Bagaimana Manajamen Talenta Mempengaruhi Retensi Karyawan: Studi Literatur - Olivia Olivia; Valerie Tanza; Viona Debataraja; Feronica Simanjorang (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research aims to explore how talent management impacts employee retention. This research uses quantitative and qualitative approach with literature review as the data collection method, so the data obtained is secondary data. Based on the 10 research articles that have been collected, talent management strategy influences employee retention, which is also related to employee satisfaction and engagement in an organization. The results showed that employee satisfaction and employee engagement positively influence employee retention. Employee satisfaction and involvement can be in the form of work fields that match their skills and knowledge, compensation given in accordance with workload, superior leadership and organizational culture, supervisor support and attention, as well as supportive communication in the work environment. The conclusion is that it is important for organizations to implement effective talent management strategies in managing their employees.